Synergistic Therapeutic Effects of Low Dose Decitabine and NY-ESO-1 Specific TCR-T Cells for the Colorectal Cancer With Microsatellite Stability - Yu, Ganjun; Wang, Wenying; He, Xiaobo; Xu, Jia; Xu, Rongrong; Wan, Tao; Wu, Yanfeng (Frontiers in Oncology, 2022)
Patients of colorectal cancer (CRC) with microsatellite stability (MSS) show poor clinical response and little beneficial result from the immune-checkpoint inhibitors, due to the ‘cold’ tumor microenvironment. Meanwhile, decitabine can drive the ‘cold’ microenvironment towards ‘hot’ in multiple ways, such as upregulating the tumor associated antigen (TAA) and human leukocyte antigen (HLA) molecular. NY-ESO-1, one of the most important TAAs, can be observably induced in tumor by low dose decitabine, which provides ideal targets for antigen specific T cell receptor engineered T (TCR-T) cells. We innovatively used a synergistic tactic, combining decitabine and NY-ESO-1 specific TCR-T cells, for fighting the MSS CRC. Firstly, we confirmed the lysing effect of the NY-ESO-1 TCR-T cells on the NY-ESO-1+ and HLA-A2+ cells in vitro and in vivo. In A375 tumor-bearing mice, the results showed that NY-ESO-1 TCR-T cell therapy could inhibit A375 tumor growth and prolonged the survival time. Furthermore, the synergistic effect of decitabine and NY-ESO-1 TCR-T cells was shown to induce even higher percentage of tumor cell being lysed in vitro than other control groups, and more potent tumor inhibition and longer survival time were observed in vivo. The innovative synergistic therapeutic strategy of decitabine and TCR-T cells for the CRC with MSS may be also effective in treatment of other epithelial malignancies. Decitabine may likewise be adopted in combination with other cellular immunotherapies.